"Anybody on this list that you're more worried about?" Qualitative analysis exploring the functions of questions during end of shift handoffs. Issue 2 (27th July 2015) - O'Brien, Colleen M; Flanagan, Mindy E; Bergman, Alicia A; Ebright, Patricia R; Frankel, Richard M
Abstract : Background: Shift change handoffs are known to be a point of vulnerability in the quality, safety and outcomes of healthcare. Despite numerous efforts to improve handoff reliability, few interventions have produced lasting change. Although the opportunity to ask questions during patient handoff has been required by some regulatory bodies, the function of questions during handoff has been less well explored and understood. Objective: To investigate questions and the functions they serve in nursing and medicine handoffs. Research design: Qualitative thematic analysis based on audio recordings of nurse-to-nurse, medical resident-to-resident and surgical intern-to-intern handoffs. Subjects: Twenty-seven nurse handoff dyads and 18 medical resident and surgical intern handoff dyads at one VA Medical Center. Results: Our analysis revealed that the vast majority of questions were asked by the Incoming Providers. Although topics varied widely, the bulk of Incoming Provider questions requested information that would best help them understand individual patient conditions and plan accordingly. Other question types sought consensus on clinical reasoning or framing and alignment between the two professionals. Conclusions: Handoffs are a type of socially constructed work. Questions emerge with some frequency in virtually all handoffs but not in a linear or predictable way. Instead, they arise in the moment, as necessary, and without preplanning. A checklist cannot model this process element because it is a static memory aid and questions occur in a relational context that is emergent. Studying the different functions of questions during end of shift handoffs provides insights into the interface between the technical context in which information is transferred and the social context in which meaning is created.